On the Performance of Noma Systems with Different User Grouping Strategies - Li, Jinqiang; Chen, Hsiao-Hwa; Guo, Qing (IEEE wireless communications, 2024)
This article investigates several critical issues on the ergodic sum capacity and system outage performance of downlink non-orthogonal multiple access (NOMA) systems with different numbers of users per cluster sharing the same resource. The outcomes from this work suggest that NOMA systems with more users per cluster perform better under a low channel gain, while those with fewer users per cluster perform better under a high channel gain. It discloses a fact that a traditional NOMA system with a fixed user grouping scheme may not be a good choice to deal with complex channel conditions with diverse applications. To address the issue, this article introduces a concept of mixed user grouping NOMA, which outperforms OMA and traditional NOMA significantly. The work in this article lays a foundation for more further investigations on mixed user grouping NOMA systems.